Wind-driven pyroelectric energy harvesting device. (11th November 2016) - Xie, Mengying; Zabek, Daniel; Bowen, Chris; Abdelmageed, Mostafa; Arafa, Mustafa
Abstract: Pyroelectric materials have recently received attention for harvesting waste heat owing to their potential to convert temperature fluctuations into useful electrical energy. One of the main challenges in designing pyroelectric energy harvesters is to provide a means to induce a temporal heat variation in a pyroelectric material autonomously from a steady heat source. To address this issue, we propose a new form of wind-driven pyroelectric energy harvester, in which a propeller is set in rotational motion by an incoming wind stream. The speed of the propeller's shaft is reduced by a gearbox to drive a slider-crank mechanism, in which a pyroelectric material is placed on the slider. Thermal cycling is obtained as the reciprocating slider moves the pyroelectric material across alternative hot and cold zones created by a stationary heat lamp and ambient temperature, respectively. The open-circuit voltage and closed-circuit current are investigated in the time domain at various wind speeds. The device was experimentally tested under wind speeds ranging from 1.1 to 1.6 m s −1 and charged an external 100 nF capacitor through a signal conditioning circuit to demonstrate its effectiveness for energy harvesting. Unlike conventional wind turbines, the energy harvested by the pyroelectric material is decoupled from the wind flow and no mechanical power is drawn from the transmission; hence the system can operate at low wind speeds (<2 m s −1 ).